2016
DOI: 10.1103/physrevlett.117.160402
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Time-Invariant Coherence in a Nuclear Magnetic Resonance Quantum Simulator

Abstract: The ability to live in coherent superpositions is a signature trait of quantum systems and constitutes an irreplaceable resource for quantum-enhanced technologies. However, decoherence effects usually destroy quantum superpositions. It was recently predicted that, in a composite quantum system exposed to dephasing noise, quantum coherence in a transversal reference basis can stay protected for an indefinite time. This can occur for a class of quantum states independently of the measure used to quantify coheren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 64 publications
1
65
0
7
Order By: Relevance
“…This fascinating behavior was named the phenomenon of sudden transition from classical to quantum decoherence. These intriguing behaviors of freezing and sudden transition were further explored theoretically and verified experimentally [19][20][21][22][23]. Consequently, it was demonstrated that the type of initial states which exhibit such as non-trivial behaviors rely upon the feature of the decohering environment being considered.…”
Section: Introductionmentioning
confidence: 83%
“…This fascinating behavior was named the phenomenon of sudden transition from classical to quantum decoherence. These intriguing behaviors of freezing and sudden transition were further explored theoretically and verified experimentally [19][20][21][22][23]. Consequently, it was demonstrated that the type of initial states which exhibit such as non-trivial behaviors rely upon the feature of the decohering environment being considered.…”
Section: Introductionmentioning
confidence: 83%
“…These requirements are significant, but much easier than demanding direct control over two qubit operations, and correspond to the stateof-the-art in systems involving trapped ions [18][19][20], cold atoms [21,22], NMR [23][24][25] or superconducting circuits [26,27]. In these systems there already exist quantum simulators powerful enough to do simulations, and satisfy our requirements, but are not currently usable as computers as it is not known how to perform logic gates on them [2,4].…”
Section: The Schemementioning
confidence: 99%
“…In our experiment, the two-qubit system was encoded on 1 H and 13 C spin-1/2 nuclei in a chloroform (CHCl 3 ) enriched with a 13 C sample, allowing complete control of the amplitude and phase of each qubit separately [61][62][63]. Applying the pseudopure-state technique [1,[64][65][66][67], the family of states in Eq.…”
Section: Fig 1 Comparison Of the Ip P A (ρ Ab ) Versus The Ie Aliamentioning
confidence: 99%